Enteric glial cell activation protects enteric neurons from damage due to diabetes in part via the promotion of neurotrophic factor release. Issue 10 (8th May 2018) - Luo, P.; Liu, D.; Li, C.; He, W.‐X.; Zhang, C.‐L.; Chang, M.‐J.
Abstract: Background: Diabetes can result in pathological changes to enteric nervous system. Our aim was to test the dynamic changes of enteric neurons and identify the role of enteric glial cells (EGCs) in regulating enteric neuron expression in diabetic rats. Methods: A single injection of streptozotocin (STZ) was used to establish diabetic rats. Animals were randomly distributed into diabetic 1‐, 4‐, 8‐, and 16‐week groups, as well as age‐matched control groups. The PGP9.5‐ and glial fibrillary acidic protein (GFAP)‐immunopositive cells were quantified by immunohistochemistry. The protein levels of PGP9.5, ChAT, nNOS, S‐100β, and c‐fos were determined by western blotting. The levels of nerve growth factor (NGF), neurotrophin 3 (NT‐3), and glial cell‐derived neurotrophic factor (GDNF) were tested by ELISA. Key Results: An increase in blood glucose and a decrease in body weight were observed following STZ administration. PGP9.5 expression did not change in the diabetic ileum. However, ChAT increased after 16 weeks, and nNOS decreased after 8 and 16 weeks in the ilea of diabetic rats. The absence of degeneration of enteric neurons during the acute stage of the disease could be the consequence of the up‐regulation of GFAP, S‐100β, and c‐fos. Moreover, the content of NGF, NT‐3, and GDNF in the ileum increased by varying degrees after 1 and/or 4 weeks of diabetes. Using 2 co‐culture models of EGCs and SH‐SY5Y cells in a high glucose condition, the supportive role of EGCs was further confirmed. Conclusions & Inferences: Enteric glial cell activation can protect enteric neurons from damage due to diabetes in the acute stage of the disease, in part via the promotion of neurotrophin release. Abstract : Diabetes can result in pathological changes to the enteric nervous system. However, the dynamic changes of enteric neurons and the role of EGCs in regulating enteric neuron expression in rats with diabetes have not been elucidated. We found that EGC activation protected enteric neurons from damage due to diabetes in the acute stage of the disease, in part via the promotion of neurotrophin release. The protective effect of EGCs in diabetic neuropathy provides further direction on disease intervention in humans.